A virtual reality craving study in tobacco addiction: The role of non-pharmacological support in tobacco detox therapy - Zamboni, Lorenzo; Campagnari, Simone; Giordano, Rosaria; Fusina, Francesca; Carli, Silvia; Congiu, Alessio; Barbon, Isabella; Melchiori, Silvia; Casari, Rebecca; Tedeschi, Elisa; Vesentin, Roberta; Verlato, Giuseppe; et al. (Frontiers in Psychiatry, 2022)
Nicotine addiction is a widespread, worldwide epidemic, causing six million deaths per year. A large variety of treatments for smoking cessation are currently available, including Cytisine, which is a promising drug due to its low cost and high safety levels. Notwithstanding the important amount of research on tobacco addiction treatments, smoking remains one of the most difficult substance use disorders to treat, probably also due to the fact that pharmacological treatment often overlooks other maintaining factors in this addiction, such as sensory impact and cue reactivity. To address this gap in both treatment protocols and scientific literature, we propose a study protocol in which we will compare the effects of combining Cytisine with Nirdosh, a herbal tobacco substitute, to Cytisine only in two groups of patients (C+N and C) who will also undergo exposure to four different virtual reality settings that will assess the importance of environmental cues. We will further assess mood and craving in the two samples, and include a control group taken from the general population. We expect the C+N group to report a more positive mood and a lower sensitivity to tobacco-related environmental cues.